L’industrie minière et le développement urbain en milieu nordique : l’exemple de Fermont au Québec - Simard, Martin; Brisson, Carl (Cybergeo, 2013)
The map of Quebec show a vast peninsula of more than 1,6 million km2. However, the northern territories, successively called Ungava, New Quebec and North-of-Quebec, belong to that Canadian province since 1912. From a Quebecer point of view, the process of integration of these vast spaces sparsely inhabited by Inuit and First nation people was carried out late in history. Besides, the economic cycles related to the mining industry seem to deeply affect the development of these northern regions. Thus, stagnation and decline succeed periods of massive investments, which bring the installation of large facilities, megastructures and some human settlements. Fermont is one of these towns affected by economic cycles. That unique town was designed by the architect-planner Norbert Schoenauer, in 1972. It expresses a desire to adapt northern settlements to the cold climates. This paper aims at taking stock of this frontier town, forty years after its creation. We will address the issue of long-term development and resiliency of isolated mining communities in the context of the Quebec government renewed interest toward northern territories. La carte du Québec affiche une vaste péninsule de plus de 1,6 millions de km2. Toutefois, la partie nord, successivement appelée l’Ungava, le Nouveau-Québec et le Nord-du-Québec, appartient à la Province du Québec depuis seulement 1912. Dans une perspective québécoise, le processus d’appropriation de ces vastes espaces peuplés d’Inuit et d’Autochtones s’est réalisé tardivement. Par ailleurs, les cycles économiques liés à l’industrie minière ont marqué en profondeur le développement des espaces nordiques. Ainsi, des phases de stagnation et de déclin succèdent aux périodes d’investissements massifs, avec la mise en place d’infrastructures colossales et d’établissements humains. La ville de Fermont est l’un de ces établissements soumis aux ruptures évolutives. Son plan urbain original, qui a été conçu par l’architecte-urbaniste Norbert Schoenauer en 1972, illustre une volonté ...